Microhabitats of Leaf-Dwelling Pholcid Spiders (Araneae: Pholcidae) in Selected Streams of Zamboanga del Sur, Philippines - II, Philip Noel O. Banaag; Nuñeza, Olga M. (Asian Journal of Biological and Life Sciences, 2015)
Studies on the microhabitat preferences of leaf-dwelling pholcids are yet to be generated in the Philippines. In this study, the microhabitat preferences of the 150 specimens of three leaf-dwelling pholcid genera and their association to certain microhabitats at Aurora and Ramon Magsaysay, Zamboanga del Sur were examined. The plant, Schistomatoglottis sp., through Bodenheimer’s Constancy, exhibited the highest constancy value at C= 83.62% (Constant) whileCaryota sp. showed the lowest (C = 20%).Seriation analysissuggests that the leaf-dwelling pholcids are all found in monocot plants and not microhabitat-specific. However, results from the bar diagram and Canonical Correspondence Analysis (CCA) suggest that the genus Calapnita showed a higher degree of preference to Schistomatoglottissp., whileBelisanasp. showed high preference for Homalomenaphilippinensis. Panjange sp.has high preference for Aglaonema sp.
Keywords: Belisana; Bodenheimer’s Constancy; Calapnita; Schistomatoglottis